Komunikasi Penanggulangan Risiko Wabah Covid-19 di Provinsi Banten - Idoh Hafidoh; Nina Yuliana; Ail Muldi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Covid-19 virus has spread out to Indonesia including Banten Province which causes multidimensional impacts from various sectors such as health, social, economic, and education. In risk mitigation of Covid-19 epidemic, it requires a risk communication approach, that is information exchange and views among stakeholders such as governments, industry, researchers/academics, mass media, and the community who takes apart of the Covid-19 Task Force. This study aims to determine the implementation of risk communication between Provincial government of Banten and stakeholders as well as the utilization of public health promotion media of Covid-19 epidemic mitigation risk. The theoretical basis of this research applied risk communication model proposed by William Leiss. The research was conducted using a qualitative evaluative approach with a case study method. The results of this research are 1) The Provincial Government of Banten consists of five stakeholders, they are government, industry, academics/researchers, mass media, and communities, in which every stakeholder has their own role of Covid-19 mitigation risk. The application used to communicate and coordinate are mostly perfomed virtually through Zoom and WhatsApp Groups. However, in practice, the implementation of Covid-19 mitigation risk in Banten Province is still not optimal because several stakeholders are not being involved by The Provincial Government of Banten. 2) The Provincial Government of Banten uses the strategy of above the line and below the line concerning the health promotion media to socialize and educate the public about Covid-19. However, the set of media content for health promotion still needs to be improved to be more creative, informative, up to date and raise the public opinion, so that it can fulfil the information needs of the society.